Assessing Nutritional Characteristics and Bioactive Compound Distribution in Seeds, Oil, and Cake from Confectionary Sunflowers Cultivated in Serbia - Nada Grahovac; Tanja Lužaić; Dragan Živančev; Zorica Stojanović; Ana Đurović; Ranko Romanić; Snežana Kravić; Vladimir Miklič (Foods, 2024)
Sunflower seeds are key agricultural commodities due to their nutritional and industrial value. This study aimed to analyze the distribution of targeted bioactive compounds and assess the physical properties across 27 sunflower seed genotypes, including parental lines and F1 and F2 hybrids, cultivated in Serbia. Various analytical techniques were employed to determine the chemical composition and physical characteristics of the seeds. This research revealed significant genetic variability in fatty acid profiles, with differences in polyunsaturated and saturated fatty acid levels among the genotypes. Hybrid seeds displayed variations in 1000-seed weight and bulk density compared to parental lines, which exhibited higher essential fatty acid contents and mechanical properties advantageous for industrial processing. These insights highlight the potential for refining breeding strategies to improve seed quality for specific industrial purposes. Overall, this study emphasizes the critical role of genetic selection in enhancing the nutritional and processing qualities of sunflower seeds, offering valuable perspectives for advancing agricultural and breeding practices.